UPAYA MENINGKATKAN PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA PEMBELAJARAN POWERPOINT MATERI SIFAT-SIFAT BANGUN RUANG DI KELAS V UPT SPF SD NEGERI GARUDA - Muflhiha Mustari; Nur Azmi Said (STKIP Subang, 2024)
The underlying problem of this research is that there are still students in class V who do not understand the material of building space. The description of the problem shows that it is necessary for teachers to carry out reforms in the mathematics learning process to improve student learning outcomes. Therefore, students want to make updates in the learning methods that are tried to be offered, namely by changing old learning patterns with new learning patterns that are more effective and meaningful for students. This study uses a qualitative approach with the type of classroom action research (PTK), which consists of 2 cycles. The focus of this research is the use of power point media in the learning process. The results of the research show an improvement in the learning process.